Genome wide association study of thyroid hormone levels following challenge with porcine reproductive and respiratory syndrome virus - Van Goor, Angelica; Pasternak, Alex; Walugembe, Muhammed; Chehab, Nadya; Hamonic, Glenn; Dekkers, Jack C. M.; Harding, John C. S.; Lunney, Joan K. (Frontiers in Genetics, 2023)
Porcine reproductive and respiratory syndrome virus (PRRSV) causes respiratory disease in piglets and reproductive disease in sows. Piglet and fetal serum thyroid hormone (i.e., T3 and T4) levels decrease rapidly in response to PRRSV infection. However, the genetic control of T3 and T4 during infection is not completely understood. Our objective was to estimate genetic parameters and identify quantitative trait loci (QTL) for absolute T3 and/or T4 levels of piglets and fetuses challenged with PRRSV. Sera from 5-week-old pigs (N=1792) at 11 days post inoculation (DPI) with PRRSV were assayed for T3 levels (piglet_T3). Sera from fetuses (N=1267) at 12 or 21 days post maternal inoculation (DPMI) with PRRSV of sows (N=145) in late gestation were assayed for T3 (fetal_T3) and T4 (fetal_T4) levels. Animals were genotyped using 60K Illumina or 650K Affymetrix SNP panels. Heritabilities, phenotypic correlations, and genetic correlations were estimated using ASREML; genome wide association studies were performed for each trait separately using JWAS. All three traits were low to moderately heritable (10 to 16%). Phenotypic and genetic correlations of piglet_T3 levels with weight gain (0-42 DPI) were 0.26±0.03 and 0.67±0.14, respectively. Nine significant QTL were identified for piglet_T3, on Sus scrofa chromosomes (SSC) 3, 4, 5, 6, 7, 14, 15, and 17, and collectively explaining 30% of the genetic variation (GV), with the largest QTL identified on SSC5, explaining 15% of the GV. Three significant QTL were identified for fetal_T3 on SSC1 and SSC4, which collectively explained 10% of the GV. Five significant QTL were identified for fetal_T4 on SSC1, 6, 10, 13, and 15, which collectively explained 14% of the GV. Several putative immune-related candidate genes were identified, including CD247, IRF8, and MAPK8. Thyroid hormone levels following PRRSV infection were heritable and had positive genetic correlations with growth rate. Multiple QTL with moderate effects were identified for T3 and T4 levels during challenge with PRRSV and candidate genes were identified, including several immune-related genes. These results advance our understanding of growth effects of both piglet and fetal response to PRRSV infection, revealing factors associated with genomic control of host resilience.